Towards the establishment of cash waqf microfinance fund for refugees - Omar Ahmad Kachkar (ISRA International Journal of Islamic Finance, 2017)
Purpose: This paper aims to propose cash waqf (endowment) to develop a conceptual model that can be utilised to extend microfinance for refugees. Design/methodology/approach: Qualitative method is used in this research. An extensive review of the literature has been conducted. Latest literature on refugees, microfinance has been critically examined beside the current cash waqf models. Findings: Empirical studies have shown that many refugees are equipped with marketable skills and talents that can be utilised to improve their socio-economic situations. The proposed model - cash waqf refugee microfinance fund (CWRMF) - is structured to extend microfinance to potential refugee micro entrepreneurs. To address the lack of collateral, which is a requirement to gain any microfinance, CWRMF has been incorporated with a takaful unit (cooperation) by which refugees may guarantee each other. Additionally, the model has also been structured to address the challenge of sustainability of the institution that would provide microfinance. Hence, a reserve fund has also been integrated into the model. Practical implications: CWRMF represents a potential model to be implemented by humanitarian non-governmental organisations (NGOs) and aid agencies to support livelihood of refugees in particular for Muslim refugees. Positive outcome is expected from the implementation of this model. This is because of the various advantages of microfinance programs not only on refugees but also on concerned NGOs, host populations and donor parties. Additionally, this paper is a set of primarily thoughts aims to open the door wider for more researchers to explore the potential of cash waqf as one of the instruments to finance refugee microenterprises and business activities. Originality/value: Recently cash waqf has been into several models for socio-economic development and poverty alleviation. This paper is proposing cash waqf as a source for a microfinance fund that can contribute in the improvement of socio-economic situations of millions of refugees around the world.
Keywords: 330; Refugee; Cash waqf; Microfinance